Novel Bacterial Strains for Nonylphenol Removal in Water and Sewage Sludge: Insights from Gene Expression and Toxicity - Alba Lara-Moreno; Inés Aguilar-Romero; Fernando Madrid; Jaime Villaverde; Jorge D. Carlier; Juan Luís Santos; Esteban Alonso; Esmeralda Morillo (Applied Sciences, 2025)
4-Nonylphenols (4-NPs) are persistent endocrine disruptors frequently found in wastewater treatment plant (WWTP) effluents and sewage sludge. This study evaluated the ability of eight bacterial strains that were isolated from sewage sludge to degrade 4-n-NP in an aqueous solution. Bacillus safensis CN12, Shewanella putrefaciens CN17, and Alcaligenes faecalis CN8 showed the highest degradation rates, removing 100%, 75%, and 74% of 4-n-NP (10 mg L⁻1), with DT50 values of 0.90, 8.9, and 10.4 days, respectively. Despite the reduction in 4-n-NP concentrations, ecotoxicity assays revealed that the resulting transformation products (TPs) were more toxic than the parent compound. To investigate the potential degradation mechanisms, in silico and gene expression analyses were conducted on B. safensis CN12, revealing a significant upregulation of the multicopper oxidase gene, cotA (7.25-fold), and the ring-cleaving dioxygenase gene, mhqO (13.9-fold). Although the CN12 strain showed potential for mineralization based on gene expression studies, this was not observed in the aqueous solution. However, when 4-n-NP was adsorbed on sludge and treated with CN12 in the presence of hydroxypropyl-β-cyclodextrin (HPBCD) as a bioavailability enhancer, mineralization reached up to 33%, indicating a synergistic effect with the native sludge microbiota.